STUDY KOMPARASI KOMUNIKASI INTERPERSONAL PADA KELUARGA POLIGAMI SATU ATAP DENGAN BEDA ATAP - Rendi Limantara; Mochtar W. Oetomo (Jurnal Komunikasi, 2015)
This study discusses the comparison of interpersonal communication in a polygamous family one roof with different roof with communication theory interpersonal.Jenis penelitihan assessment is descriptive qualitative where this penelitihan does not intend to investigate the hypothesis, but the events that are the reality of the status of people or objects with a set of conditions or thought.This study uses deskriptifkualitatif used by researchers to decipher any information / data obtained through interviews, observation, and documentation in a polygamous family which is the object of this research. Triangulation of sources and methods that help researchers to test the validity of the data that has been obtained.Results from this study is that interpersonal communication is done by Mr. Dof to both his wife is more dominant and intense with kedua.Bapak Dof wives and families, including those who openly (except Mas Hanif) .Berbeda with Mr. Mohc more closed during interpersonal communication with anyone even conditional to talk about the relationship berkeluarganya. The conflict is not considered a problem that threatens because it can be solved by good communication as a step completion.Keywords: Study Komparasi, Komunikasi Interpersonal, Poligami